Adubação com mangânes em cultivares de soja: efeito de doses e fontes aplicadas via foliar - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
Manganese (Mn) is a micronutrient because it is demanded in small quantities, but it is essential for plants, playing important roles in different vital processes such as water photoxidation in Photosystem II and is an enzymatic cofactor, responsible for the activation of more than 35 different enzymes. The objective of this study was to evaluate the effects of applications of Manganese via leaf on the productive and nutritional aspects of soy. The work was developed in the agricultural year 2019/20, being conducted at Fazenda Capão Grande in the municipality of Cristalina, Goiás. The soil of the experimental area is classified as Red-Yellow Latosol. After soil analysis, pH correction was not carried out, only fertilization according to technical recommendations for the crop. The cultivars CD2728IPRO and M7739IPRO were sown on November 7, 2019. Throughout the experiment, a factorial scheme (5 x 3) + 1 was adopted, with the first factor corresponding to the doses, the second the sources and an additional one without application of the nutrient via leaf. The design used was in randomized blocks, with four replications. The sources Mn used were Mn sulfate, Mn chelated with EDTA and Mn oxide ground into particles of micrometric scale in suspension. The doses of Mn tested were 25%, 50%, 75%, 100% and 125% of the recommended dose of 350 g ha-1 of Mn. Each experimental unit was composed of four lines 6 m long, spaced 0.50 m apart. The two central lines were considered useful, minus 0.5 m at each end. Application of manganese via leaf influences the levels of leaves and grains of this micronutrient in soybean culture. However, the agronomic characteristics of soybeans do not change significantly when submitted to applications of manganese via leaf. The two soybean cultivars showed different responses to applications of manganese via leaf. The weight of a thousand grains and the height of insertion of the first pod in cultivar M7739IPRO, were influenced by the doses of manganese applied via leaf.
Manganese fertilization in soybean cultivars: effect of doses and sources applied via foliar
Keywords: Micronutriente; Nutrição de plantas; Glycine max; Produtividad; Micronutrient; Plant nutrition; Glycine max; Productivity; CIENCIAS AGRARIAS; FISIOLOGIA VEGETAL::NUTRICAO E CRESCIMENTO VEGETAL